Association between self-esteem and depression in hearing-impaired adolescents - Umme Amara; Dr Barerah Siddiquii; Nida Rasheed (University of Wah Journal of Social Sciences, 2024)
The purpose of this research was to investigate the relationship between self-esteem and depression in hearing-impaired adolescents at Deaf Reach School, Karachi Campus. In light of earlier literature, it was hypothesized that there would be a high prevalence of low self-esteem and depression in hard-of-hearing adolescents and a negative relationship between low self-esteem and depression in deaf adolescents. For this research, 60 students of the adolescent age group range (M= 30, F= 30) were chosen through convenient sampling at Deaf Reach School, Karachi Campus. Proper ethical considerations were maintained, and permission was taken from concerned individuals for data collection. Adolescent Self Esteem Questionnaire and Siddiqui Shah Depression Scale were used for this research. Findings indicated a high prevalence of low self-esteem (55%) and a consecutively high incidence of depression (49%) in hearing-impaired adolescents. Moreover, the research proved that a moderate negative relationship exists between low self-esteem and depression among hearing-impaired adolescents (r= -0.575, p= 0.05). The study has implications for educational institutions, psychologists, and counselors for managing self-esteem and depression in hearing-impaired students.